STATUS GIZI, AKTIVITAS FISIK, PERSEPSI MANFAAT, DAN HAMBATAN PEMENUHAN ASUPAN GIZI ORANG DENGAN HIV/AIDS - Sidjabat, Forman Novrindo; Triatmaja, Nining Tyas; Bevi, Amelia (GIZI INDONESIA, 2021)
One of the efforts to improve the quality of life of people living with HIV/AIDS (PLWHA) is to maintain optimal nutritional status so that it can increase immunity to infection and disease, increase energy and be more productive. This study aims to describe the nutritional status, physical activity, and perceived benefits and barriers to fulfilling the nutritional intake of people living with HIV/AIDS (PLWHA). This research was a descriptive study using mixed methods. Data were collected on 5 female PLWH informants using a 2x24 hour food recall to determine consumption patterns and measure nutritional status based on BMI and the adequacy of nutritional intake (macro includes energy, protein, fat, carbohydrates; and micro including Vit. A, Vit. B, Vit. C, Zn); and the calculation of physical activity used the Physical Activity Level (PAL). In-depth interviews were conducted to explore perceived the benefits and barriers of PLWHA to fulfilling their nutritional needs and were analyzed using the Rapid and Rigorous Qualitative Data Analysis technique with triangulation informant. The BMI status of informants was 3 normal informants, 1 overweight informant, and 1 obese informant. Types of physical activity carried out were 4 informants doing light physical activity and 1 informant doing moderate physical activity. The frequency of eating the seams of informants is 3 times a day and the number of informants with normal adequacy of fat and energy intake is 1 informant each and 2 informants protein, carbohydrate nutrition intake is not sufficient. The adequacy of normal micronutrients is vitamin b for 2 informants, vitamin c, and b for 1 informant each. The informants know that nutrients can increase immunity, but the types of consumption by the informants have not varied. Assistance services, counseling, and nutrition education are also needed during the HIV / AIDS treatment process.ABSTRAKSalah satu upaya meningkatkan kualitas hidup Orang dengan HIV/AIDS (ODHA) adalah mempertahankan status gizi optimal sehingga dapat meningkatkan kekebalan terhadap infeksi dan penyakit, peningkatan energi dan akan lebih produktif. Penelitian ini bertujuan untuk menggambarkan status gizi, aktivitas fisik, serta persepsi manfaat dan hambatan pemenuhan asupan gizi orang dengan HIV/AIDS (ODHA). Penelitian ini merupakan penelitian deskriptif menggunakan metode campuran. Data dikumpulkan pada 5 informan ODHA perempuan dengan menggunakan food recall 2x24 jam untuk mengetahui pola konsumsi dan mengukur status gizi berdasar pada IMT dan kecukupan asupan gizi (makro meliputi energi, protein, lemak, karbohidrat; dan mikro meliputi vitamin A, vitamin B, vitamin C, Zn); perhitungan aktivitas fisik menggunakan Physical Activity Level (PAL). Wawancara mendalam dilakukan untuk menggali persepsi manfaat dan hambatan ODHA mencukupi kebutuhan gizi dan dianalisa menggunakan teknik Rapid and Rigorous Qualitative Data Analysis dengan informan triangulasi. Status IMT informan adalah 3 informan normal, 1 informan gemuk, dan 1 informan obesitas. Jenis aktivitas fisik yang dilakukan adalah 4 informan melakukan aktivitas fisik ringan dan 1 informan melakukan aktivitas fisik sedang. Frekuensi makan keliman informan sebanyak 3x sehari dan jumlah informan dengan kecukupan normal pada asupan lemak dan energi masing-masing 1 informan dan protein sebanyak 2 informan, asupan gizi karbohidrat tidak tercukupi. Kecukupan gizi mikro normal adalah vitamin B pada 2 informan, vitamin C dan B masing-masing 1 informan. Informan mengetahui zat gizi dapat meningkatkan kekebalan tubuh tapi jenis konsumsi informan belum beragam. Diperlukan juga layanan pendampingan, konseling dan edukasi gizi, selama proses pengobatan HIV/AIDS.Kata kunci: HIV/AIDS, ODHA, angka kecukupan gizi